2020
DOI: 10.1186/s11671-020-3283-5
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesized Phytochemically (Zingiber officinale and Allium sativum) Reduced Nickel Oxide Nanoparticles Confirmed Bactericidal and Catalytic Potential

Abstract: Phyto-synthesized nanoparticles (NPs) having reduced chemical toxicity have been focused globally and become essential component of nanotechnology recently. We prepared green phytochemically (ginger and garlic) reduced NiO-NPs to replace synthetic bactericidal and catalytic agent in textile industry. NPs were characterized using ultraviolet visible spectroscopy (UV-Vis), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Fourier-transform infrared spectroscopy (FTIR), energy-dispersive X-ray spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 170 publications
(79 citation statements)
references
References 43 publications
5
70
0
Order By: Relevance
“…Moreover, no sensible changes have been observed in peak position when the sample stored up to 6 months in the laboratory, indicating high stability of bioproduced NiO NPs in aqueous green media. Previous studies reported the optical absorption peak of biological NiO NPs in the range of 330-350 nm using green synthesis methods 17,18,30 which are in good agreement with our results.…”
Section: Uv-visible Spectroscopy Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, no sensible changes have been observed in peak position when the sample stored up to 6 months in the laboratory, indicating high stability of bioproduced NiO NPs in aqueous green media. Previous studies reported the optical absorption peak of biological NiO NPs in the range of 330-350 nm using green synthesis methods 17,18,30 which are in good agreement with our results.…”
Section: Uv-visible Spectroscopy Analysissupporting
confidence: 92%
“…Among these tremendous efforts, nickel oxide nanoparticles have been developed as an efficient catalyst in chemical synthesis of a wide range of valuable organic compounds such as spiro and condensed indole derivatives 11 , aromatic heterocycle 12 , 5-substituted 1htetrazoles 13 , quinolines 14 , and spirooxindoles 15 . There are a variety of green methods that have been addressed the construction of the nickel oxide nanoparticles (NiO NPs), mostly relied on plant-assisted bioreduction strategy [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Significant zones of inhibition recorded for SnO (250, 500 and 750 °C) samples for E. coli and S. aureus ranged Size, concentration and morphology of nanostructures directly affects oxidative stress produced. Antibacterial activity imperiling size and concentration portrays inverse relation to size [68][69][70]. Nanostructures more efficiently produce reactive oxygen species (ROS) which exist in bacterial membrane resulting cellular organelles extrusion and bacteria death [71].…”
Section: Resultsmentioning
confidence: 99%
“…Nanotechnology is a potential interdisciplinary science, has a broad range of promising utilization in biomedicine and biotechnology (Naz et al, 2018; Qamar, Asgher, Khalid, & Sadaf, 2019). It facilitates the field of biomedicine by using nanoparticles (NPs) through various physical and chemical processes (Aqeel et al, 2020; Haider et al, 2020a; Mansoor et al, 2017; Pourebrahim et al, 2018; Somasundaram, Rajan, Sangaiya, & Dilip, 2019). However, innovations toward sustainable and ecofriendly routes of synthesis are need of hour (Imran et al, 2018; Jeyaraj et al, 2013; Naz et al, 2017; Zangeneh, Zangeneh, & Moradi, 2020).…”
Section: Introductionmentioning
confidence: 99%